Maternity care experience of Pakistani ethnic minority women in Hong Kong - Asim, Saba; Nichini, Elena; Goggins, William Bernard; Dong, Dong; Yeoh, Eng-King (Frontiers in Public Health, 2023)
Background: Persistent inequalities in maternity care experience and outcomes exist globally for ethnic minority (EM) and migrant women. Despite the fact that this is an important research area, no prior study has been done in Hong Kong (HK) to examine maternity care experience of EM women. Objectives: To investigate maternity care experience of Pakistani EM women (both local born and immigrants) during pregnancy, birth and after birth in hospital in HK. An evaluation of their satisfaction and factors predicting satisfaction with care during the three phases of maternity care was included in the study. Methods: A cross sectional survey was conducted among Pakistani EM women who had given birth in HK in last three years, using a structured questionnaire by a bilingual interviewer, from April to May 2020. Counts and percentages were used to describe all categorical variables. Association between predictor variables and overall satisfaction was assessed by bivariate analysis and multiple logistic regression. Results: One hundred and twenty questionnaires were completed. Almost sixty percent of the women were very satisfied with the overall care. Only about two-thirds of women described the care as kind, respectful and well communicated. After adjusting for age and parity, HK born, having higher self-described English-speaking ability and some university or above education were significant predictors of relatively less satisfaction. Conclusions: Maternity care providers should take into account the diversity of EM women population in HK. Our findings suggest that effective communication and care that can meet individual needs, expectations, and values is imperative to improve experience and quality of maternity care for EM women in HK.